PLAY, RISK AND ECONOMIC ANALYSIS BASED ON SUBSURFACE DATA TO DECIDE FIELD DEVELOPMENT STRATEGY, PAGARDEWA AREA, SOUTH SUMATRA BASIN - Adhi Nugroho, Suprayitno
The development of hydrocarbon exploration in the Pagardewa area, South Sumatra Basin begins with discovery of Kuang structure in 1940, followed by some exploration drilling on Pagardewa and Prabumenang structure with less encouraging results. The lack of effort to develop the field at the moment was constrained by the low price of oil and gas discovery that has not got market, therefore had a major effect to the economic structure. After the additional of the data which is based on the rising of world oil prices in the early 1990s, the exploration activities began to re-active through discovery in Tasim, Karangdewa and Pemaat structure which followed by additional 3D seismic data in 2007 to reduce the subsurface risks and uncertainties. Efforts to optimize the subsurface data (well and seismic data) in the area to recognize the potential as well as uncertainties related to the development plan through play, risk, and economic analysis, so it can defined the right development strategy related to the actualization of the additional reserves, accelerating the discovery to the production phase, an integrated field development and investment effectiveness which has been and will be done. The results of play, risk and economic analysis shows it still has exploration potential supported with high success ratio of drilling with average 80% and low geological risk with average 48%. Based on economic analysis for all structure total NPV USD 233,412,945; IRR average 80.7%; PI average 2.02 dan POT 8 years. Decision tree analysis shows that there is a group of structures that have eligibility to be developed soon. Integration of the results analysis that has been done through spider/radar diagram plots makes a comprehensive portfolio perspective, which would be base decisions on field development strategy as well as the optimization value of the investments made.